ANÁLISE DO DESEMPENHO HIGROTÉRMICO DE PAREDES DE FACHADA POR MEIO DE SIMULAÇÃO COMPUTACIONAL ESTUDOS DE CASO - Santos, Alexandre Cordeiro; Oliveira, Luciana Alves; Becere, Osmar Hamilton; Souza, Julio Cesar Sabadini (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The moisture can make the building environment unhealthy and affecting the user's health and the durability of building and furniture. Current Brazilian technical standards are still insufficient to deal with this issue and one of the alternatives is the computer simulation, which, although limited, can be useful. The aim of this manuscript is to show the results of the hygrothermal assessment (temperature and moisture content) of the two facades section of two different buildings, which is part of the case studies. This assessment was done through computer simulation with WUFI-Pro software. The follow activities were done: Bibliographical review, laboratory tests for collecting the hygrothermal characteristics of the building materials used in the facades of the case studies and collected of the temperature and moisture in the apartments (housing) of the case studies. The use of a computer simulation to evaluate the moisture transfer through a wall is feasible. The data obtained show that the percentage of moisture occurrence in the case studies is consistent with the results obtained in the simulation.